Beyond transfusions and transplants: genomic innovations rewriting the narrative of thalassemia - Shi, Liangbin; Yan, Xili; Xia, Yanwei; Zhao, Yingdi; Zhu, Xiuling; Li, Qiang; Xu, Zhiliang (Annals of hematology, 2025)
Thalassemia is a globally prevalent inherited blood disorder that usually leads to severe complications and even premature death due to impaired hemoglobin synthesis. The conventional treatment approach encompasses a range of interventions, including red blood cell transfusions, iron chelation therapy, splenectomy, and allogeneic hematopoietic stem cell transplantation. However, transfusion-induced iron overload and the limitation of graft matching have emerged as significant clinical impediments. In recent years, with the advent of precision medicine and translational research, the treatment of thalassemia has undergone a paradigm shift toward stem cell gene therapy, gene editing combined with nanodelivery, and pharmacogenomics-guided, personalized treatment regimens. In preclinical and early-phase clinical trials, these approaches have demonstrated efficacy in modulating hemoglobin gene expression and reversing ineffective hematopoiesis. Consequently, this review explores the constraints imposed by conventional therapeutic approaches and the advancements in the field of gene therapy for thalassaemia. It elucidates the mechanisms of gene editing and the potential of stem cell therapies. Furthermore, the discourse encompasses the advancement of primary prevention strategies, including genetic testing and prenatal screening, in the context of reducing morbidity. It is our hope that this review will provide the latest clues and insights in gene therapy for the effective management of thalassemia.